Sustainability of Forage Systems in Small Holder Dairy Cattle in The Plateau in East Java - Rahardjo, L.; Wadjdi, M.F. (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. This study aimed to describe the sustainability of forage system in the small holder dairy cattle in the plateau in East Java, in particular related to the nutrient content. The method used was survey (interviews, questionnaires, field observations and sampling) at the cooperation unit, farmers, livestock and farming location in one of the areas of dairy cattle cooperation in the plateau (Cooperation of SAE Pujon-Malang). The data obtained were analyzed through descriptive and regression statistics. The results showed that forage system dominantly given during dry and rainy seasons are elephant grass and corn stalks. Linear regression equation for the nutrient content of elephant grass is TDN= 40.516 + 1.404 CP, while corn trees is TDN= 56.212 + 0.740 CP. The conclusion showed that the dependent variable is largely influenced by external factors (environment). Improved continuity of availability of forage can be done by increasing the feeding system in the region (plateau) as well as the support from outside the region. Key words: plateau, dairy cattle, forage Abstrak. Penelitian ini bertujuan untuk mendiskripsikan keberlanjutan sistem pakan hijauan pada peternakan sapi perah rakyat di wilayah dataran tinggi di Jawa Timur, khususnya tentang kandungan nutrisi. Metode yang digunakan adalah survei (wawancara, pengisian angket/kuesioner, observasi, dan pengambilan sampel) di koperasi, petani ternak dan lokasi peternakan di salah satu wilayah koperasi persusuan di dataran tinggi (Koperasi SAE Pujon-Malang). Data yang didapat dianalisis dengan regresi dan statistik diskriptif. Hasil penelitian menunjukkan bahwa pakan hijaun yang dominan di musim kemarau dan hujan adalah rumput gajah dan tebon jagung. Persamaan regresi linier untuk kandungan nutrisi rumput gajah adalah TDN= 40,516 + 1,404 PK, sedangkan tebon jagung adalah TDN= 56,212 + 0,740 PK. Kesimpulannya adalah variabel dependen sebagian besar dipengaruhi oleh faktor luar (lingkungan). Peningkatan kontinuitas ketersediaan pakan hijauan dapat dilakukan dengan peningkatan sistem pakan di wilayah (dataran tinggi) dan dukungan sistem pakan dari luar wilayah. Kata kunci: dataran tinggi, sapi perah, pakan hijauan